Mineralization of pig slurry compost treated with retorted oil shale and dicyandiamide in two contrasting soils - Monteiro, Luanna Corrêa; Aita, Celso; Schirmann, Janquieli; Pujo, Stefen Barbosa; Giacomini, Diego Antônio; Paust, Kathleen da Silva; Silveira, Carlos Augusto Posser; Giacomini, Sandro José (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate carbon and nitrogen mineralization in the soil after the application of composts produced in an automated composting plant, using pig slurry (PS) with and without the addition of retorted oil shale (ROS) and dicyandiamide (DCD) during composting. Laboratory studies were carried out for 180 days on two soils with contrasting characteristics: sandy-loam Typic Paludalf and clay Rhodic Hapludox, which were managed for more than 10 years under a no-tillage system. The composts were thoroughly mixed with the soils. The mineralization of the C and N from the compost was evaluated by measuring continuously CO2 emissions and periodically mineral N (NH4+ + NO3-) content in the soils, respectively. The mineralization of the C from the compost without ROS and DCD was higher in the sandy-loam soil (20.5%) than in the clay soil (13.9%). Similarly, 19.4% of the total N from the compost was mineralized in the sandy-loam soil and 10.9% in the clay soil. The presence of ROS in the compost reduced C mineralization by 54%, compared with the treatment without additives, in the sandy-loam soil and caused net N immobilization in both soils during incubation. The addition of DCD during PS composting did not affect the mineralization of the C and N from the compost in both soils. The addition of ROS during the composting of PS favors the retention of the C from the compost in the soil, especially in the sandy-loam one, but results in a net N immobilization.